Fiscal Underpinnings for Sustainable Development in China Rebalancing in Guangdong (Springer Singapore, 2018)
This book collects high-quality papers on issues related to the rebalancing strategy in China, new clean cities as "hubs'', liability management, and involving the private sector, including through PPPs, with specific examples from Guangdong. Guangdong has been at the forefront of economic reforms in China since the advent of the Responsibility System in the late 1970s, and its successes and challenges reflect those of China as a whole. The need for rebalancing towards a more inclusive and sustainable path is also critical in Guangdong, just as it is in China. Strengthening the fiscal underpinnings and the next stages of tax reforms are critical drivers to accomplishing the requisite structural changes.